Factors Associated with Treatment Adherence of Brazilian Patients Undergoing Hemodialysis - Nakao, Renata Tamie (Universidad de Costa Rica, 2016)
Objetivo: Evaluar la adherencia de pacientes al tratamiento de la hemodiálisis (HD) y su relación con variables psicosociales. Método: Participaron 64 pacientes adultos con HD, evaluados en cuanto a depresión, ansiedad, apoyo social, conocimiento de la enfermedad y del tratamiento, y la adherencia. Resultados: Hay asociación entre sexo y adherencia a la HD, la dieta y la medicación, así como entre escolaridad y la adherencia general. Hay asociación entre niveles de conocimiento de la enfermedad y depresión con la adherencia a la restricción de líquidos. No se encontró asociación entre la adherencia y la ansiedad. Conclusión: La identificación de los determinantes de la adherencia al tratamiento es esencial para la elaboración de estrategias eficaces para mejorar la calidad de vida de los pacientes.Abstract: To evaluate patients’ adherence to hemodialysis (HD) and its relationship to psychosocial variables. Methods: 64 adult patients undergoing HD participated in the study and were assessed in regard to depression, anxiety, social support, disease and treatment knowledge, and adherence. Results: Association between sex and adherence to HD, and to diet and medication was found, as well as between schooling and overall adherence. There is association between disease knowledge and depression, with adherence to fluid restrictions. No association was found between adherence and anxiety. Conclusion: Identifying the determinants of treatment adherence is essential to devise efficacious strategies to improve patients’ quality of life.